Biology and civil engineering proceedings of the conference held at the Institution, September 1948. (Institution of Civil Engineers, 1949)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in September 1948.